KAGHOMBO SEBAGAI NILAI- NILAI PENDIDIKAN BAGI ANAK PEREMPUAN DI KECAMATAN WATOPUTE KABUPATEN MUNA - La Ode Darfin; Eko Harianto (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2017)
This study aimed to describe the process of performing Kaghombo ritual that contain special advices about character education of Muna ethnic community in Kecamatan Watopute, Muna Regency. This study used a qualitative approach to describe process of ritual’s implementation with observation technique and depth interview to the intervieews. The result showed that Kaghombo’s process in Kariya tradition in Muna ethnic began from Kaalano oe, Alano Bhansa, Polobha, Kakadiu, Kabasano Haroa, Kafoluku and Kabansule. There are three types of character education which is contain in advices of education’s character that exist in KaghomboofKariya tradition; 1) Nemotehi all deeds are forbidden by Allah SWT, as dont tell a lie, can control his lust, and no other people's rights; 2) Kafekatangka is an important advices of the strength and strength of faith to not be tempted with the luxury of the world such as photoro, infasu, dosabhara, and dotawakala; 3) Polambu is the advice about married life, which concerns the obligation of a wife to husband and duty of a wife who must be able to carry out his family and husband.